Impact of integrated use of enriched compost, biochar, humic acid and Alcaligenes sp. AZ9 on maize productivity and soil biological attributes in natural field conditions - Hussain, Azhar; Ahmad, Maqshoof; Mumtaz, Muhammad Zahid; Nazli, Farheen; Farooqi, Muhammad Aslam; Khalid, Imran; Iqbal, Zafar; Arshad, Hadeeqa (Italian Journal of Agronomy, 2019)
Organic amendments improve the soil quality and plant productivity as well as help in the establishment of introduced bacteria. The present study was conducted to evaluate the interactive impact of organic amendments and plant growth promoting rhizobacteria strain Alcaligenes sp. AZ9 to improve maize productivity and soil quality. organic amendments including rock phosphate enriched compost (RPEC), biochar, and humic acid were applied in soil along with and without Alcaligenes sp. AZ9. The results revealed that the sole application of organic amendments along with Alcaligenes sp. AZ9 showed increase in growth and grain yield of maize. However, a combined application of organic amendments (RPEC, biochar, and humic acid) along with Alcaligenes sp. AZ9 showed maximum increase in plant height up to 14%, shoot dry biomass up to 30%, 1000-grains weight up to 10%, grain yield up to 31%, stover yield up to 34%, and potassium (K) concentration in grains up to 12% as compared to absolute control. The increase in nitrogen (N) and phosphorus (P) concentration in grains was non-significant over control. This treatment also improved soil biological attributes in terms of the bacterial population up to 60%, microbial biomass carbon up to 22%, soil organic carbon up to 29%, and saturation percentage of soil up to 14% as compared to control. It can be concluded that the application of organic amendments improved establishment of introduced bacteria, which could be effective in improving maize growth and yield as well as soil health.